2012
DOI: 10.1093/carcin/bgs276
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of liver carcinogenesis by amarogentin through modulation of G 1 /S cell cycle check point and induction of apoptosis

Abstract: Amarogentin, a secoiridoid glycoside, is an active component of the medicinal plant Swertia chirata. In this study, chemopreventive and chemotherapeutic actions of amarogentin were evaluated in a carbon tetrachloride (CCl(4))/N-nitrosodiethylamine (NDEA)-induced liver carcinogenesis mouse model system during continuous and posttreatment schedule. Better survival, no toxicity and increased body weight were noted in amarogentin-treated mice. Reduction in proliferation and increase in apoptosis frequency were evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 35 publications
3
36
0
1
Order By: Relevance
“…Similar data has not yet been reported. However, increase in RBSP3 and LIMD1 expression, along with down-regulation of pRB expression has been reported in chemoprevention of liver carcinogenesis in mouse by amarogentin (Pal et al, 2012). On the other hand, reduced expression of cMYC in some post-therapy tumors (5/11) indicates the importance of this gene in inhibition of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar data has not yet been reported. However, increase in RBSP3 and LIMD1 expression, along with down-regulation of pRB expression has been reported in chemoprevention of liver carcinogenesis in mouse by amarogentin (Pal et al, 2012). On the other hand, reduced expression of cMYC in some post-therapy tumors (5/11) indicates the importance of this gene in inhibition of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our studies on three main targets of the C/EBP␤-HDAC1 complexes: p53, SIRT1, and PGC1␣, and on consequences of the down-regulation of p53 at late stages of liver cancer. It has been shown that the p53-p21 pathway inhibits liver proliferation and that it is eliminated during development of liver cancer (23,24). However, the mechanism of this elimination has not been shown.…”
Section: Discussionmentioning
confidence: 99%
“…15 Additionally, a dose of 0.2 mg/g has been reported to elicit a good response in HCC mice. 8,9 Thus, a 0.2 mg/g/d dose was selected for the animal experiments. A 5 Â 10 6 (0.2 mL) aliquot of HepG2 cells was injected subcutaneously into the left flank of each mouse.…”
Section: Treatment Of the Tumor Modelsmentioning
confidence: 99%